Modified Tubularized Incised Plate (TIP) Urethroplasty in Distal Penile Hypospadias - A Tertiary Care Experience (GAIMS Journal of Medical Sciences, 2026)
Background: After the advent of the Snodgrass tubularized incised plate (TIP) urethroplasty technique for the correction of distal penile hypospadias and urethroplasty complications like urethrocutaneous fistula, meatal stenosis, and glans flap dehiscence in 2% of cases in the year 1994, it became a popular technique among hypospadias surgeons for the correction of distal penile hypospadias irrespective of the intrinsic clinical parameters. The issue of the thin membranous distal urethra, inadequate urethral plate, small conical glans and associated complications following the TIP procedure are well described. Objectives of the study were to find out the surgical procedure undertaken and the outcomes in distal penile hypospadias in our institute. Materials and Methods: This is a retrospective study on distal penile hypospadias operated on in the department of plastic surgery of our institute from April 2017 to March 2022. Results: The present study had a total of 96 boys with distal penile hypospadias; ages ranged from 2 years to 26 years, with a mean age of 5.02 years and a standard deviation of 3.47 years. It was found that 84 (87.5%) of cases of distal penile hypospadias were managed with the modified TIP procedure, and 12 (12.5%) cases were managed with Byars' stage procedures. It was found that 64 (66.7%) of the outcomes were uneventful, and in 32 (33.3%) cases, urethroplasty complications were noted, consisting of preputial flap loss in 3.1%, glans flap dehiscence in 9.4%, meatal stenosis in 9.4%, urethrocutaneous fistula in 8.3% of cases, meatal stenosis with fistula in 1%, and urethral stricture in 1 (2.1%) of cases. Conclusion: Tubularized incised plate urethroplasty, or its modified version of including an extra 3mm to 4mm of penile skin lateral to the urethral plate on either side, is found suitable in the majority (87.5%) of the cases of distal penile hypospadias but not all.